Spacelike hypersurfaces in de Sitter space with constant higher-order mean curvature - Kairen Cai; Huiqun Xu (International Journal of Mathematics and Mathematical Sciences)
The authors apply the generalized Minkowski formula to set up a spherical theorem. It is shown that a compact connected hypersurface with positive constant higher-order mean curvature Hr for some fixed r , 1≤r≤n, immersed in the de Sitter space S1n+1 must be a sphere.